2020
DOI: 10.1111/jam.14593
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of comammox bacteria in the sediments of an urban lake

Abstract: Aims Although comammox have been discovered in a variety of ecosystems, there are few studies in urban lakes. This paper attempted to confirm whether this ammonia‐oxidizing microbe exists in urban lakes and to determine the factors influencing its existence. Methods and Results This study investigated the diversity and abundance of comammox bacteria in sediments of a typical urban lake in China, and their ecological relationship with other ammonia‐oxidizing micro‐organisms. The phylogenetic analysis indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…For example, a study of multiple groundwater-fed sand filters recovered 12 comammox MAGs (5 clade A and 7 clade B) and revealed the co-occurrence of at least five comammox species (10 on average) per system (34). Other studies in soils, sediments, lakes, drinking water, groundwater, and estuaries have also reported the co-existence of multiple comammox species (9,73,93,94 while the three systems in this study have influent ammonia concentrations between 2 and 3 mM.…”
Section: Microdiversity Of Nitrifying Bacteriamentioning
confidence: 99%
“…For example, a study of multiple groundwater-fed sand filters recovered 12 comammox MAGs (5 clade A and 7 clade B) and revealed the co-occurrence of at least five comammox species (10 on average) per system (34). Other studies in soils, sediments, lakes, drinking water, groundwater, and estuaries have also reported the co-existence of multiple comammox species (9,73,93,94 while the three systems in this study have influent ammonia concentrations between 2 and 3 mM.…”
Section: Microdiversity Of Nitrifying Bacteriamentioning
confidence: 99%
“…In addition, OTU 7 and OTU 124 in the same lineage (clade A.1) had high homology with the sequences of comammox Nitrospira from wetland soil of Qinghai-Tibetan plateau and lake sediment, respectively 9 , 48 . The sequences of OTU 49, OTU 44, and OTU 11 in clade A.2 had high homology with the sequences of comammox Nitrospira from estuary tidal flat wetland, alpine glacier-forefield soil and lake sediment, respectively 10 . The sequences of OTU 4 in clade B had high similarity with the sequences of comammox Nitrospira from forest soils (> 95%, 1000 replicates) 57 .…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have revealed a wide existence of comammox Nitrospira in freshwater and terrestrial ecosystems such as basin 9 , lake 10 , riparian ecosystem 11 , coastal wetland 12 , agricultural soil 13 , and forest soil 14 . Comammox Nitrospira have also been found in engineering environments including drinking water systems 6 , 15 , wastewater treatment systems 16 , 17 and activated sludge 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Rifle soils, AOA was 3.8‐ to 10.5‐fold higher than comammox Nitrospira , as revealed through metagenomic studies [13,91]. Three species of clade A comammox Nitrospira were detected from urban lake sediments in China, This study demonstrates the role of comammox bacteria in the nitrification of the urban lake and the inverse relationship between the growth of comammox and eutrophication [92]. For better management of the nitrification process, it is necessary to know the ecophysiological parameters that are controlling the function of comammox Nitrospira .…”
Section: Ecophysiologymentioning
confidence: 89%